Tinjauan Yuridis Terhadap Pemanfaatan Mediasi Sebagai Alternatif Penyelesaian Sengketa Dalam Hukum Acara Perdata di Indosenia - Safira Putri Zakia (JURNAL MULTIDISIPLIN ILMU AKADEMIK, 2025)
The utilization of mediation as an alternative dispute resolution in civil procedural law in Indonesia has become increasingly important with the rising number of disputes submitted to the courts. This study aims to analyze the effectiveness of mediation in resolving disputes and identify the challenges faced in its implementation. The method employed is qualitative literature study, reviewing various laws and previous research related to mediation. The findings indicate that mediation offers quicker and more cost-effective solutions, as well as helps maintain good relationships between the disputing parties. However, challenges such as low legal awareness among the public and a lack of mediator skills need to be addressed to optimize mediation as a dispute resolution method. The conclusion of this study emphasizes that mediation is a valid option and should be promoted in the practice of dispute resolution in Indonesia